2014
DOI: 10.1016/j.jaging.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Residential normalcy and environmental experiences of very old people: Changes in residential reasoning over time

Abstract: The decision to relocate in old age is intricately linked to thoughts and desires to stay put. However, most research focuses either on strategies that allow people to age in place or on their reasons for relocation. There is a need for more knowledge on very old peoples' residential reasoning, including thoughts about aging in place and thoughts about relocation as one intertwined process evolving in everyday life. The aim of this study was to explore what we refer to as the process of residential reasoning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 28 publications
5
54
0
Order By: Relevance
“…Rather they hope their children will return, and, if they do not, they will just continue to miss them. This is consistent with the broader international literature which suggests that older individuals prefer to stay where they had been and age in place (Granbom et al, 2014).…”
Section: Emotional Supportsupporting
confidence: 91%
“…Rather they hope their children will return, and, if they do not, they will just continue to miss them. This is consistent with the broader international literature which suggests that older individuals prefer to stay where they had been and age in place (Granbom et al, 2014).…”
Section: Emotional Supportsupporting
confidence: 91%
“…This can be explained, at least in part, by the fact that they have been developed within a medical model, resembling hospitals rather than a home (Hauge & Heggen, 2007). Care is provided as efficiently as possible to accommodate large numbers of people, and so nursing homes typically lack certain core qualities of home such as control, autonomy, choice, privacy and self-determination (Cooney, 2012;Custers, Westerhof, Kuin, Gerritsen, & Riksen-Walraven, 2012;Granbom et al, 2014;Kasser & Ryan, 1999;Persson & Wasterfors, 2009;Stabell, Eide, Solheim, Solberg, & Rustoen, 2004). As a result, it is difficult for many older adults to make themselves 'at home' in a nursing home (Granbom et al, 2014;Shin, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Care is provided as efficiently as possible to accommodate large numbers of people, and so nursing homes typically lack certain core qualities of home such as control, autonomy, choice, privacy and self-determination (Cooney, 2012;Custers, Westerhof, Kuin, Gerritsen, & Riksen-Walraven, 2012;Granbom et al, 2014;Kasser & Ryan, 1999;Persson & Wasterfors, 2009;Stabell, Eide, Solheim, Solberg, & Rustoen, 2004). As a result, it is difficult for many older adults to make themselves 'at home' in a nursing home (Granbom et al, 2014;Shin, 2014). Several studies have found that the core qualities of home are positively linked to the well-being of older people, including those in longterm care settings (Boyle, 2008;Cooney, 2012;Sixsmith et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Still, these findings show that a move to a new dwelling can trigger the need for a HA. But, most importantly, the thoughts on moving/staying put are influenced by several intertwined aspects [36] that rejecting HA grant application due to thoughts on moving, might not promote ageing-in-place. In clinical practice, it is important to remember that the HA intervention is directed at one person in a couple, but it impacts on the residential reasoning of both, which highlights the importance of viewing the couple as a unit [37].…”
Section: Housing Decisionsmentioning
confidence: 99%